Temporal dynamics of SO2 and NOX pollution and contributions of driving forces in urban areas in China. (November 2018) - Zhao, Shuang; Liu, Shiliang; Hou, Xiaoyun; Cheng, Fangyan; Wu, Xue; Dong, Shikui; Beazley, Robert
Abstract: SO2 and NOX pollution have significantly reduced the air quality in China in past decades. Haze and acid rain have negatively affected the health of animals, plants, and human beings. Documented studies have shown that air pollution is influenced by multiple socioeconomic driving forces. However, the relative contributions of these driving forces are not well understood. In this study, using the structural equation model (SEM), we quantified the contributing effects of various forces driving air pollution in 2015 in prefecture-level cities of China. Our results showed that there has been significant control of SO2 pollution in the past 20 years. The annual average SO2 concentration has dropped from 83 μg/m 3 in 1996 to 21 μg/m 3 in 2015, while the annual average NOX concentration has increased from 47 μg/m 3 in 1996 to 58 μg/m 3 in 2015. We evaluated data on the annual average concentrations of SO2, which in some cities may mask the differences of SO2 concentrations between different months. Hence, SO2 pollution should continue to be controlled in accordance with existing policies and regulations. However, we suggest that NOX should become the new focus of air pollution prevention and treatment. The SEM results showed that industrial scale, city size, and residents' activities have a significant impact on NOX pollution. Among these, industrial scale had the highest contribution. The findings from our study can provide a theoretical basis for the formulation of NOX pollution control policy in China. Graphical abstract: Image 1 Highlights: SO2 pollution has been controlled effectively. NOX pollution became the new focus of prevention and control in 2015. Industrial scale had the strongest impact on urban NOX pollution. Ten recommendations to control NOX pollution are proposed. Abstract : Using the structural equation model we quantified the effects of various forces driving NOX pollution in 2015 in prefecture-level cities of China.